Improving The Nutrition of Pregnant Village Women in Indonesia The Important Roles of Village Midwives and Cadres - Setyowati, Setyowati (Jurnal NERS, 2015)
Introduction: The maternal mortality remains high in developing countries such as Indonesia. Three most common reasons for this incidence are hemorrhage, infection, and eclampsia. Some of these conditions can be infl uenced by Iron Defi ciency Anemia (IDA). A lot of programs for nutrition have been provided by Indonesian government, but the nutritional condition of pregnant women still be big problem in Indonesia. This study explored the nutritional status of pregnant village women in Banten Province, Indonesia and assessed interventions in dealing with nutrition problems among pregnant women especially in the rural area. Method: The design was a longitudinal descriptive study with operational study by empowering village midwives and cadre to intervene pregnant women nutrition in rural area. The measurements were focused on the rate of anemia, body mass index (BMI), and weight. Three stages were applied in this study with community development as intervention. Result: This study reported some changes in the midwife practises after Intervertion, while cadres more talkative when explaining about nutrition after intervention. However, the intervention did not affect the overall nutritional status of the pregnant women and the intervention was not able to influence the communityâs health in the medium term in the intervention villages. Analysis and discussion: This study recommend the government and educational institutions to improve the competencies of health care providers especially in communication skill.Â Keywords: Community development, Indonesia, nutritional status, pregnant women, rural nursing.